Extensive and objective wine color classification with chromatic database and mathematical models. (10th January 2018) - Li, Si-Yu; Zhu, Bao-Qing; Li, Li-Jun; Duan, Chang-Qing
ABSTRACT: Theoretic conjecture and mathematical models used for classifying wines into different chromatic levels were examined, based on a comprehensive chromatic database of 237 dry red wines. Similar mathematical models were also built for 79 Chinese Cabernet Sauvignon dry red wines from different regions and vintages, which could be set as chromatic reference for other Chinese Cabernet Sauvignon dry red wines. The reliability of these models and relationships between different chromatic parameters were further validated by statistical tools. Such methodology can be adopted to build chromatic references for wines from different backgrounds, thus to classify wine color more extensively and objectively.